Rate dependent behavior of crash-optimized adhesives – Experimental characterization, model development, and simulation. (January 2015) - May, Michael; Hesebeck, Olaf; Marzi, Stephan; Böhme, Wolfgang; Lienhard, Jörg; Kilchert, Sebastian; Brede, Markus; Hiermaier, Stefan
Highlights: Extensive material characterization. Development of a new fully-rate dependent material model for cohesive elements. Rate dependency of damage initiation stress. Rate dependency of fracture toughness. Considering strain-rate history. Abstract: The mechanical properties of crash-optimized adhesive BETAMATE 1496V are characterized over a wide range of strain rates. The information gathered from the mechanical tests are used for developing a fully rate-dependent constitutive law for cohesive interface elements considering both, the strain rate dependency of the initiation stress and the strain rate dependency of the fracture toughness. The model is calibrated and verified against experimental data for tapered double cantilever beam (TDCB) and tapered end notched flexure (TENF) tests. Finally, the model is validated against quasi-static and dynamic experimental results on an adhesively bonded T-joint. The numerical predictions show good correlation with the experimental results.